IoT Home Guard: Enhancing Security for Smart Home Privacy and Protection - Souvik Sikdar; Samya Das; Soham Dey; Radha Krishna Jana (International Journal of Computer Sciences and Engineering, 2023)
The advent of smart homes using IoT has transformed the way households operate, providing convenience and efficiency to residents. However, the integration of IoT devices in the home network also creates security risks that may compromise the privacy and safety of individuals and households. This research paper provides an analysis of the security risks associated with smart homes using IoT, including hacking, unauthorized access, data breaches, device vulnerabilities, and insecure networks. The study also discusses the impact of these security risks on households and individuals, such as financial losses, privacy violations, physical harm, and emotional distress. The research design utilized a qualitative approach, including a literature review and interviews with experts in the field. The findings of the research emphasize the need for implementing strong security measures, such as strong passwords, two-factor authentication, encryption, and regular software updates, to mitigate the security risks associated with smart homes using IoT.